Non-Cognitive Diagnostic Assessment Instrument of Learning Interest Based on Website for Elementary School Students - Hairida; Hartoyo, Agung; Pranata, Rio; Munawar; Fatmadiwi, Anggi (Universitas Pendidikan Ganesha, 2024)
The availability of standard integrated diagnostic assessment tools for measuring students' learning interests with technology for the Entikong border area is not yet available, so an instrument is needed to help educators measure students' initial assessments. This study aimed to analyze non-cognitive diagnostic assessments of website-based learning interests. The Research and Development (R&D) method was used in this study, with three stages of activity, namely Need Analysis & Design, Development, and Evaluation. The subjects of validation were 10 assessment experts and five website graphic experts. A limited trial for practicality testing was carried out during the Evaluation stage. The instruments used were interview guidelines, validity questionnaires, and response questionnaires for practicality testing. Data analysis was quantitative and qualitative, using the Lawshe formula to measure validity. The results showed that the assessment developed had an average CVR value of 0.99 and 1 with a valid category and a practicality test of 93.75% with a convenient category. This study concludes that the non-cognitive diagnostic assessment instrument for website-based learning interests developed meets the requirements for validity and practicality. This research implies that educators can use the website-based non-cognitive diagnostic assessment instrument as a reference in designing learning according to student needs based on the Independent Curriculum.